Molecular identification of Sinonovacula constricta, Sinonovacula rivularis and their interspecific hybrids using microsatellite markers - Wang, Shasha; Shi, Yi; Dong, Yinghui; Meng, Yiping; Yao, Hanhan; He, Lin (Frontiers in Marine Science, 2024)
The razor clam Sinonovacula constricta, is one of the most commercially important cultured bivalves in China and Southeast Asia, while S. rivularis is its closer relatives discovered more than a decade ago. In order to obtain offspring with faster growth rate and stronger salt tolerance of S. constricta and S. rivularis, interspecific hybrids were produced, and the hybridity of the interspecific hybrids was confirmed by microsatellite markers. Microsatellite markers exhibit a high potential for transfer through cross-amplification in related species, and the transferability of 48 pairs of microsatellite marker primers from S. constricta were assessed in S. rivularis. Here, 24 universal microsatellite markers were successfully amplified in S. rivularis, of which 18 were polymorphic with the allele number from 2 to 5. The genetic diversity of two razor clams evaluated by 18 polymorphic microsatellite markers indicated that two species were both above the middle level, with a relatively higher genetic diversity, while S. constricta showed higher genetic diversity than S. rivularis according to the genetic parameters of Na, Ho, He and PIC. Furthermore, a total of two species-specific microsatellite markers were screened, which could be used for quick genetic identification of S. constricta, S. rivularis and their hybrids. The results suggest the induced interspecific hybrids are true hybrids between S. constricta and S. rivularis, which provide a basis for breeding, subsequent protection, and germplasm resources utilization of the razor clams.